Synthesis of substituted Z-styrenes by Hiyama-type coupling of oxasilacycloalkenes: application to the synthesis of a 1-benzoxocane - Vyvyan, James R.; Engles, Courtney A.; Bray, Scott L.; Wold, Erik D.; Porter, Christopher L.; Konev, Mikhail O. (Beilstein Journal of Organic Chemistry, 2017)
Several Hiyama cross-coupling reactions of oxasilacycloalkenes and aryl iodides are described that produce trisubstituted Z-styrenes in moderate to excellent yields. Both electron-rich and electron-poor aryl iodides are tolerated in the cross-coupling reaction. The oxasilacycloalkene coupling partners were prepared by ruthenium-catalyzed intramolecular anti-hydrosilylation of alkynols. One of the cross-coupling products was converted to a 1-benzoxocane, albeit in low yield, using an intramolecular Buchwald–Hartwig etherification. The cyclic ether produced contains the carbon skeleton of heliannuol A.
Keywords: cross-coupling; heterocycles; hydrosilylation; palladium; silicon